Lexical and morphological development: a case study of Malay English bilingual first language acquisition - Mohamed Salleh, Rabiah Tul Adawiyah; Di Biase, Bruno; Kawaguchi, Satomi (Sciendo, 2021)
Many first language acquisition (FLA) studies have found a strong correlation between lexical and grammatical development in early language acquisition. For bilingual first language acquisition (BFLA), the development of grammar is also found to be correlated with the size of the lexicon in each language. This case study investigates how a Malay-English bilingual child developed the lexicon and grammar in each of her languages and considers possible evidence of interaction between the languages during acquisition. The study also aims to show that the predominant linguistic environment to which the child was alternatively exposed might have played an important role in her lexical and grammatical development. Thus, the study presents two sets of data: (a) a 12-month longitudinal investigation when the child was 2;10 up till 3;10 in Australia and (b) a one-off elicitation session at age 4;8 when the family was in Malaysia. The findings show that not only the emergence of grammar is linked to the lexical size of the developing languages, but that other variables, mainly the linguistic environment and the bilingual language mode, also influenced the child’s language productions.